Egyptian Liberalism Reassessed: Muhammad ’Abdallah ’Inan’s Response to German Nazism: 1933-1935 - Gershoni, Israel (جماعة, 1999)
Egyptian intellectual history between the two World Wars has been the focus of much scholarly work. The main thrust of many of the studies on the subject has been directed toward an understanding of what is known in the literature as "the crisis of orientation" in the intellectual discourse of the 1930s. Two hegemonic narratives constituted the basis for the different interpretations given the "crisis of the intellectuals". The first narrative saw the crisis as a testimony to the intellectuals’ total withdrawal from Western liberal values. The second, revisionist narrative saw the intellectuals’ shift to writing on Islamic subjects as a tactical maneuver aimed at neutralizing popular Islamic pressures on these intellectuals. This article attempts to deconstruct the two traditional narratives through a critical examination of the "crisis story". The article shows that the two narratives’ usage of the Islamiyyat literature as an exclusive source for describing and understanding the "intellectual crisis" is both reductionist and simplistic. By examining a different textual corpus of the Egyptian intellectuals in the 1930s, the study claims that they did not withdraw from liberal positions and values but, on the contrary, substantiated and adhered to them. The anti-fascist and anti-Nazi texts by Muhammad ’Abdallah "Inan well represent Egyptian liberalism and its established status within the intellectual discourse.